A NEW TROPICAL SPECIES OF TRIPOSPORIUM - Rifai, Mien A. (REINWARDTIA, 1972)
An illustrated description of Triposporium novoguineensei Rifai sp. nov. is presented based on a specimen collected at Garaina, New Guinea.A special visitor award from the Australian Government enabled me to attend the 42nd Australian and New Zealand Association for the Advancement of Science (ANZAAS) Congress held in August 1970 in Port Moresby (Territory of Papua and New Guinea), and to participate in a botanical and agricultural post-congress tour around the Territory. The ample opportunity to collect fungi during this tour was fully utilized and a specimen which appeared to represent an undescribed species of Triposporium was found in Garaina Tea Estate, Garaina, Territory of Papua.